Synthesis and electrophosphorescence of novel heteroleptic iridium complexes based on thiazole-containing ligands. Issue 41 (7th April 2016) - Liu, Di; Yao, Ruijuan; Fu, Min; Li, Deli; Zhang, Shufen
Abstract : Novel heteroleptic iridium complexes containing aromatic-ring-fused-thiazole in cyclometalating ligands are developed and exhibit a maximum external quantum efficiency of 22.2% in orange phosphorescent organic light-emitting diodes. Abstract : Three novel heteroleptic cyclometalated iridium complexes, namely Ir-Cz, Ir-DBF and Ir-Np, were designed and synthesized for use as emitters in organic light-emitting diodes (OLEDs). 2-Phenyl-(aromatic-fused-thiazole) (the aromatic is carbazole, dibenzofuran or naphthalene) was designed as the major cyclometalating ligand framework to enlarge the ligand conjugate length and to study its influence on the photophysical and electrochemical properties and electroluminescent performances of iridium complexes. The three heteroleptic complexes containing acetylacetonate (acac) as an ancillary ligand emit orange to orange-red phosphorescence with a small bathochromic shift in comparison with the reference complex bis(2-phenylbenzothiozolato-N, C 2 ′)iridium(acetylacetonate) [Ir-Bt]. They all exhibited good performance in phosphorescent OLEDs. In particular, a maximum current efficiency of 54 cd A −1, a peak power efficiency of 34 lm W −1 and an external quantum efficiency of 22.2% were realized for Ir-Np based devices.